EVALUATION OF BIOLOGICAL EFFICACY OF AMARANTHUS HYBRIDUS (L.) LEAF EXTRACTS AGAINST SPODOPTERA LITURA (L.) AND THREE STORED PRODUCT PESTS - RAN, PATHIPATIUSHA; VIJAYA, MOVVA. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2016)
Acetonic extracts of Amaranthus hybridus (L.) were evaluated for toxicity and insect antifeedant activity against the third instar larvae of Spodoptera litura (F.) by surface application method and leaf disc bioassays. Also against the adults of three stored product pests such as Sitophilus Oryzae (L.), Rhyzopertha dominica (F.) and Tribolium castaneum (Herbst) by filter paper diffusion method (direct contact application) and fumigation methods. The insect responses towards the treatment depended on the concentrations of the test compound and also with the mode of application. The results of antifeedant bioassays showed that the highest percentactivity occurred at a concentration of 125mg/100 pil against S. litura (78.2%). The mortality rates for stored product pests were calculated using probit analysis and highest activity was observed against R. dominica (76%), followed by S. oryzae (64%) and T. castaneum (60%). These results suggested that botanical extract of A. hybridus exhibited promising insecticidal activity against agricultural and stored product pests, hence, can be considered for further developing it for the usage in pest management strategies.